2020
DOI: 10.1038/s41598-020-69208-3
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection, a risk factor for Type 2 diabetes mellitus: a hospital-based cross-sectional study among dyspeptic patients in Douala-Cameroon

Abstract: Diabetic mellitus patients are usually prone to chronic infections. However, there have been contradictory reports about the association between H. pylori infection and type II diabetes. The present study is aimed at evaluating the prevalence of Helicobacter pylori infection among type 2 dyspeptic diabetic patients in the littoral region of Cameroon. This cross sectional study comprised 93 type 2 diabetic dyspeptic patients and 112 non-diabetic dyspeptic patients attending the Gastroenterology Department at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…Similar results of seroprevalence H. pylori showed in Vietnam 48.8% (Nguyen et al, 2017), Nigeria 28.0 and 36.3% (Samson et al, 2018;Daniyan et al, 2020). However, the results obtained in this study is lower than those of previous studies of anti-H. pylori seropositivity 98% (Misganaw and Abera, 2017), 64.39% (Mabeku et al, 2018), 51.4% (Chukwuma et al, 2020), 73.11 and 58.05% for dyspeptic diabetic patients and non-diabetic respectively (Mabeku et al, 2020), and fecoprevalence 81.8% (Sabh and El-Less, 2017). The reason for this variation could be due to difference in sample size, diagnostic methods, sanitation practice level of individuals and communities, living conditions or low levels of exposure to the risk factors other than that included in our study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Similar results of seroprevalence H. pylori showed in Vietnam 48.8% (Nguyen et al, 2017), Nigeria 28.0 and 36.3% (Samson et al, 2018;Daniyan et al, 2020). However, the results obtained in this study is lower than those of previous studies of anti-H. pylori seropositivity 98% (Misganaw and Abera, 2017), 64.39% (Mabeku et al, 2018), 51.4% (Chukwuma et al, 2020), 73.11 and 58.05% for dyspeptic diabetic patients and non-diabetic respectively (Mabeku et al, 2020), and fecoprevalence 81.8% (Sabh and El-Less, 2017). The reason for this variation could be due to difference in sample size, diagnostic methods, sanitation practice level of individuals and communities, living conditions or low levels of exposure to the risk factors other than that included in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…The data were confirmed by multivariate logistic regression analysis. Similar results of other studies revealed that H. pylori infection was associated with dyspepsia (Misganaw and Abera, 2017;Tameshkel et al, 2018;Borges et al, 2019;Mabeku et al, 2020). Other study showed the predictor of seroprevalence H. pylori was found to be epigastric pain (Hamrah et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…In terms of obesity, most of the reported meta-analyses sustain a significant positive association between H. pylori and obesity risk [ 159 , 165 , 167 ] ( Table 2 ). Moreover, a recent study from Douala-Cameron showed that H. pylori and high body mass index, separately or not, were proven to be risk factors for diabetes mellitus [ 81 ]. Contrarily, Alzahrani et al found a relationship only between H. pylori infection and increased body mass index and not with type 2 diabetes mellitus [ 83 ].…”
Section: H Pylori Infection Insulin Resistance Diabetes Mell...mentioning
confidence: 99%
“…Another study administered salidroside (50 mg/kg/day and 100 mg/kg/day) to STZ-induced type 2 diabetic rats (that had been fed on a HFD for 4 weeks) for six weeks; analysis showed that both mechanical allodynia and thermal hyperalgesia were alleviated. Analysis also showed that salidroside relieved type 2 diabetes mellitus (T2DM) by improving hyperglycemia and by ameliorating insulin resistance [ 79 ]; these results were critical because T2DM is characterized by hyperglycemia and insulin resistance [ 95 ].…”
Section: The Antinociceptive Effect Of Glycosides In a Rodent Model Of Neuropathic Painmentioning
confidence: 99%